2022
DOI: 10.1002/smll.202203140
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress of Advanced Conductive Metal–Organic Frameworks: Precise Synthesis, Electrochemical Energy Storage Applications, and Future Challenges

Abstract: inherent disadvantage of unstable output, which means electrochemical energy storage and conversion devices are essential for storing and utilizing these energies at any time. [6] Supercapacitors (SCs), lithium-ion batteries (LIBs), lithium-sulfur (Li-S) batteries, and electrochemical water splitting can efficiently convert electricity into chemical energy for storage and thus have received extensive attention. [7] The performance of the energy storage devices mainly depends on the electrode materials and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(16 citation statements)
references
References 156 publications
0
16
0
Order By: Relevance
“…Hydro/solvothermal synthesis is a liquid-phase chemical reaction in a sealed pressure vessel with water or other solvents under certain conditions. [120] Controlling the reaction conditions, such as the solvent, temperature, and volume, can adjust the morphology and crystal structure of conductive MOFs. Interface-assisted synthetic routes, including liquid-liquid, liquid-solid, and gas-liquid interfacial approaches.…”
Section: Design and Synthesis Strategies Of Conductive 2d Mofsmentioning
confidence: 99%
“…Hydro/solvothermal synthesis is a liquid-phase chemical reaction in a sealed pressure vessel with water or other solvents under certain conditions. [120] Controlling the reaction conditions, such as the solvent, temperature, and volume, can adjust the morphology and crystal structure of conductive MOFs. Interface-assisted synthetic routes, including liquid-liquid, liquid-solid, and gas-liquid interfacial approaches.…”
Section: Design and Synthesis Strategies Of Conductive 2d Mofsmentioning
confidence: 99%
“…The hydro/solvothermal method is one of the most common preparation methods for self-supporting MOFs with high crystallinity and various morphologies in an autoclave over a wide temperature range (100–200 °C). 50 Surface oxygen groups and defects on the surface of conductive substrates favor MOF's nucleation and conformal growth, which facilitates the uniform deposition and solid bonding of MOFs on conductive substrates. Yang et al reported self-supporting Co/Zn-based ZIF (ZIF = zeolitic imidazolate framework) nanosheets on Ni foam (NF) through a facile hydrothermal method (Fig.…”
Section: Synthesis Strategiesmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs), an emerging type of crystalline porous material, are coordination networks assembled from organic ligands and metal joints. Owing to their excellent characteristics, such as large specific surface area, excellent thermal durability, and tunable structure and topology, , MOFs have been increasingly employed in applications such as pollutant elimination, , separation, catalysis, energy storage, , and adsorption. , However, because water molecules can gradually replace organic ligands through ligand exchange or hydrolysis, some MOFs become unstable in the presence of humidity. , Manipulating wettability to prepare hydrophobic MOFs is a feasible way to prevent water-sensitive MOFs from decomposing in high humidity, which can significantly broaden the application scope of MOFs. …”
Section: Introductionmentioning
confidence: 99%